3D hierarchical CoO@MnO2 core–shell nanohybrid for high-energy solid state asymmetric supercapacitors. Issue 1 (5th December 2016) - Li, Chao; Balamurugan, Jayaraman; Thanh, Tran Duy; Kim, Nam Hoon; Lee, Joong Hee
Abstract : The 3D CoO@MnO2 core-shell nanohybrid based asymmetric supercapacitors deliver an excellent energy density (~85.9 Wh kg −1 ), an ultra-high power density (~16769 W kg −1 at 51.7 Wh kg −1 ), and remarkable cycle stability (86.8% capacitance retention after 10 000 cycles). Abstract : A unique morphology, high specific surface area, extraordinary porosity, and excellent conductive networks are typical favorable properties of pseudocapacitors; however, fully comprehending and interpreting this substantive topic still remains a great challenge. Herein, we present a new strategy for the direct growth of a cobalt monoxide@manganese oxide core–shell nanostructure on 3D Ni foam (CoO@MnO2 /Ni foam). This is accomplished by simple, scalable, in situ fabrication methods to produce a material that can be employed as an advanced electrode material for high-energy solid state asymmetric supercapacitors (ASCs). The cost-effective, binder-free 3D CoO@MnO2 core–shell nanostructure delivers excellent electrochemical properties with an ultra-high specific capacitance (1835 F g −1 at a current density of 1 A g −1 ), tremendous rate capabilities with an extraordinary capacitance of 1198 F g −1 at a current density of 20 A g −1, and outstanding stability (97.7% capacitance retention after 10 000 cycles). ASCs with a maximum potential window of 1.8 V are fabricated by using a 3D CoO@MnO2 core–shell nanohybrid as the positive electrode and N-doped graphene (NG) as the negative electrode in order to validate the outstanding performance for practical energy storage devices. Impressively, the ASCs delivered a high specific capacitance (191 F g −1 at 1 A g −1 ), excellent energy density (∼85.9 W h kg −1 ), an ultra-high power density (∼16 769 W kg −1 at 51.7 W h kg −1 ), and remarkable cycle stability (86.8% capacitance retention after 10 000 cycles). These findings provide a new method to design 3D CoO@MnO2 core–shell nanostructures that are cost-effective and binder-free electrode materials for the development of high-performance energy storage devices.